Multidisciplinary management of metastatic spine disease: initial symptom-directed management. (18th November 2020) - Steinberger, Jeremy M; Yuk, Frank; Doshi, Amish H; Green, Sheryl; Germano, Isabelle M
Abstract: In the past 2 decades, a deeper understanding of the cancer molecular signature has resulted in longer longevity of cancer patients, hence a greater population, who potentially can develop metastatic disease. Spine metastases (SM) occur in up to 70% of cancer patients. Familiarizing ourselves with the key aspects of initial symptom-directed management is important to provide SM patients with the best patient-specific options. We will review key components of initial symptoms assessment such as pain, neurological symptoms, and spine stability. Radiographic evaluation of SM and its role in management will be reviewed. Nonsurgical treatment options are also presented and discussed, including percutaneous procedures, radiation, radiosurgery, and spine stereotactic body radiotherapy. The efforts of a multidisciplinary team will continue to ensure the best patient care as the landscape of cancer is constantly changing.